A highly efficient preparation method for battery-grade monoammonium phosphate based on composite material co-catalysis

Through the combination of composite material cocatalysis and MCM-41@chitosan adsorbent, the problem of complex and high cost of battery-grade monoammonium phosphate preparation process is solved, and a high-purity, efficient preparation and environmentally friendly battery-grade monoammonium phosphate production method is achieved.

CN119735178APending Publication Date: 2025-04-01CHENGDU WINTRUE HLDG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411933292.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the prior art, the preparation process of battery-grade monoammonium phosphate is long, the control is difficult, and the production cost is high. Moreover, due to the low grade of phosphate resources in China, the impurities in wet phosphoric acid are high, which affects the production of high-purity monoammonium phosphate.

Method used

Using a method based on composite material cocatalysis, the monoammonium phosphate solution was prepared by blending and dissolving crude phosphoric acid with methanol and precipitating filtration, using an amino-activated carbon filter assembly, and adding ammonia water. At the same time, MCM-41@chitosan adsorbent was prepared, and the monoammonium phosphate solution was further purified by its high adsorption capacity and biocompatibility.

Benefits of technology

It realizes efficient preparation of battery-grade monoammonium phosphate, improves the purity and quality of the product, simplifies the process, reduces production costs, and the method is environmentally friendly and meets the requirements of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735178A_ABST
    Figure CN119735178A_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of monoammonium phosphate production, and particularly relates to an efficient preparation method for battery-grade monoammonium phosphate based on composite material co-catalysis. Crude phosphoric acid is blended and dissolved with methanol, and the filtrate is passed through a filter assembly filled with amino activated carbon to prepare MCM‑41@chitosan adsorbent, and filtered through a filter filled with MCM‑41@chitosan adsorbent to prepare battery-grade monoammonium phosphate. The present invention does not add any additional chemical substances. This additive-free production method reduces the chemical burden on the environment and avoids toxic byproducts and waste that may be produced in traditional chemical treatment methods. It not only helps to protect the environment, but also meets the current global pursuit of green chemistry and sustainable development. In this way, the preparation process of battery-grade monoammonium phosphate will not cause secondary pollution, ensuring environmental friendliness throughout the application process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of monoammonium phosphate production, and in particular relates to a method for efficiently preparing battery-grade monoammonium phosphate based on composite material co-catalysis. Background Art

[0002] Monoammonium phosphate, also known as diammonium phosphate, has a chemical formula of NH 4 H 2 PO 4 It is an important phosphorus-containing compound that can be used as a phosphate fertilizer in agriculture, as a fire retardant and an important chemical raw material in chemical production. It is widely used in papermaking, organic synthesis, lithium iron phosphate production and other fields.

[0003] Monoammonium phosphate can be used as flame retardant, feed additive, fermentation aid, bulking agent, nutrition enhancer, high-grade water-soluble fertilizer, etc., and has a wide range of applications. However, since monoammonium phosphate is mostly made of relatively expensive thermal phosphoric acid as raw material, its production process consumes a lot of energy and has high costs. Using relatively low-cost wet-process phosphoric acid as raw material to produce industrial-grade monoammonium phosphate can further improve the economic benefits of producing ammonium phosphate. The key to producing industrial-grade monoammonium phosphate through wet-process phosphoric acid is the purification of phosphoric acid. Due to the low grade of China's phosphate resources, the impurities such as Mg, Fe, and AI in the produced wet-process phosphoric acid are relatively high, which directly affects the production of high-purity monoammonium phosphate. Therefore, the production of monoammonium phosphate must first be preliminarily purified.

[0004] According to different fields of use, monoammonium phosphate can be divided into fertilizer grade (i.e. agricultural grade) monoammonium phosphate, industrial grade monoammonium phosphate and battery grade monoammonium phosphate. Among them, battery grade monoammonium phosphate, which is the raw material for lithium iron phosphate production, has a large market demand and high market value. Battery grade monoammonium phosphate has higher requirements for performance indicators such as purity, so the requirements for production process are also more stringent.

[0005] Patent CN20170026629.7 discloses a method for producing industrial-grade and battery-grade monoammonium phosphate from fertilizer-grade monoammonium phosphate. The method uses powdered monoammonium phosphate as raw material, dissolving, filtering, removing impurities with impurity removers, adjusting pH neutralization, and finally concentrating and crystallizing to prepare industrial-grade and battery-grade monoammonium phosphate. The process of this method is relatively long, and the control difficulty and production cost are relatively high.

[0006] Therefore, it is of great significance to find a method for preparing battery-grade monoammonium phosphate with a simple process, easy control and high yield. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a method for preparing battery-grade monoammonium phosphate based on composite material co-catalysis, which first adopts crude phosphoric acid and methanol to dissolve and then settle and filter, and then treats the monoammonium phosphate solution by amino activated carbon filter assembly and adds ammonia water. First, the co-dissolution of methanol helps the uniform dispersion of crude phosphoric acid and the preliminary separation of impurities, and the sedimentation process further separates insoluble impurities, thereby improving the subsequent filtration efficiency. The filtrate obtained by filtration has a high purity, which provides a good raw material basis for subsequent reactions. Then, amino activated carbon is used as a filter medium, and the rich amino functional groups on its surface can effectively adsorb residual impurities in the filtrate, further purify the filtrate, and ensure the high purity of the monoammonium phosphate solution. Finally, by accurately controlling the mass ratio of filtrate 2 to ammonia water, the pH value of the reaction system can be adjusted to promote the formation of monoammonium phosphate, while avoiding the cost increase and environmental burden caused by excessive ammonia water. The preliminary preparation process of monoammonium phosphate is completed through the above process.

[0008] In step 3, the principle of preparing MCM-41@chitosan adsorbent is based on the interaction between sodium alginate and 2-morpholineethanesulfonic acid buffer solution to form a stable solution. Through magnetic stirring, the sodium alginate molecules are evenly dispersed in the solution to form a uniform gel network structure. Subsequently, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide are added as cross-linking agents to further enhance the cross-linking between sodium alginate molecules and form a more stable gel. The addition of MCM-41 nanomolecular sieve provides a high specific surface area and porous structure, increasing the adsorption sites, while the addition of carboxymethyl chitosan introduces more active groups and enhances the chemical adsorption capacity of the adsorbent. By dripping calcium nitrate solution drop by drop, sodium alginate and calcium ions undergo ionic cross-linking to form a hydrogel. After filtration, washing and freeze-drying, the final MCM-41@chitosan adsorbent has a unique composite material structure, combining the high adsorption capacity of MCM-41 and the biocompatibility of chitosan. As a mesoporous molecular sieve, MCM-41 has a regular hexagonal pore structure and a high specific surface area, which makes it excellent in adsorption performance. After combining with chitosan, the formed MCM-41@chitosan composite material not only has the high adsorption capacity and selectivity of MCM-41, but also enhances its adsorption capacity for specific ions due to the active groups such as amino and hydroxyl groups of chitosan. This composite material can effectively remove impurities in the solution and improve the purity of monoammonium phosphate, especially in removing heavy metal ions such as Hg, Zn, Cu, Cr, Ni, Mn and other heavy metal particles. It shows efficient adsorption performance. In the preparation process of battery-grade monoammonium phosphate, the use of MCM-41@chitosan adsorbent can significantly improve the purity and quality of the product. At the same time, its good regeneration performance also helps to reduce production costs and improve economic benefits. In summary, MCM-41@chitosan adsorbent provides an efficient, environmentally friendly and economical purification route in the preparation of battery-grade monoammonium phosphate. The entire preparation process not only improves the purity and quality of monoammonium phosphate, but also achieves the dual goals of cost-effectiveness and environmental friendliness by optimizing operating conditions and material selection, providing an efficient and clean preparation method for industrial-scale production.

[0009] Finally, the preparation process of MCM-41@chitosan adsorbent is relatively simple, with high solid phase yield, high structural integrity, and reproducibility, all of which help to reduce production costs and improve the feasibility of industrial applications. The technical solution adopted to achieve the purpose of the present invention is:

[0010] A method for efficiently preparing battery-grade monoammonium phosphate based on composite material co-catalysis comprises the following steps:

[0011] Step 1, dissolving crude phosphoric acid and methanol, stirring until the mixture is uniform, settling for 0.5 to 2 hours, filtering the liquid to obtain filtrate 1;

[0012] Step 2: adding ammonia water to the filtrate 2 of the filter assembly filled with aminated activated carbon to prepare a monoammonium phosphate solution, wherein the mass ratio of the filtrate 2 to the ammonia water is 1:0.6-1;

[0013] Step 3: Dissolve sodium alginate in 2-morpholineethanesulfonic acid buffer solution, stir magnetically for 3 hours, add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide, stir magnetically for 1 to 3 hours, add MCM-41 nanomolecular sieve, ultrasonicate for 30 to 120 minutes, add carboxymethyl chitosan, continue magnetic stirring for 3 to 5 hours to obtain a mixed viscous solution, add calcium nitrate solution drop by drop, and continue to add until the color changes to white, and filter to obtain water The gel was washed with ultrapure water for 3 times, and ultrapure water was added to cover the hydrogel. After freezing with liquid nitrogen, it was immediately placed in a vacuum freeze dryer for freeze drying and dried at -60°C for 24-48h, i.e., MCM-41@chitosan adsorbent, wherein the above raw materials are calculated by mass ratio as follows: sodium alginate: 2-morpholineethanesulfonic acid buffer solution: 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride: N-hydroxysuccinimide: MCM-41 nanomolecular sieve: carboxymethyl chitosan: calcium nitrate solution

[0014] =1:50~150:0.8~9.5:1.5~4.5:1.5~5.6:2.3~10:0.5~1.5;

[0015] Step 4: Pass the monoammonium phosphate solution through a filter filled with MCM-41@chitosan adsorbent to obtain filtrate 3, and dry the filtrate 3 to obtain battery-grade monoammonium phosphate.

[0016] Furthermore, in step 1, the mass ratio of the crude phosphoric acid to methanol is 1:0.5-0.8.

[0017] Furthermore, in step three, the concentration of the 2-morpholineethanesulfonic acid buffer solution is 15 to 30 mmol / L.

[0018] Furthermore, in step three, the mass percentage of the calcium nitrate solution is 15% to 50%.

[0019] Furthermore, the preparation process of the MCM-41 nanomolecular sieve comprises the following steps:

[0020] The method comprises the following steps: preparing a mixed solution of hexadecyltrimethylammonium bromide, triethanolamine, NaOH and deionized water, stirring the solution at 400 r / min for 20 to 50 minutes at 40°C, adding white carbon black into the mixed solution and stirring the solution uniformly, adjusting the pH value of the solution to 10 to 11 with a 1 mol / L HCI solution to obtain a mixed gel, transferring the mixed solution into an open glass vessel, placing the glass vessel into the inner lining of a reaction kettle, adding 5 to 20 ml of deionized water outside the glass vessel, aging the solution at 85 to 100°C for 20 to 48 hours under steam-assisted conditions, crystallizing the solution at 150°C for 24 to 48 hours, washing and drying the solution, and calcining the solution at 500 to 550°C for 4 to 8 hours to obtain an MCM-41 nano molecular sieve.

[0021] Due to its unique mesoporous structure and active groups of chitosan, MCM-41@chitosan adsorbent has efficient adsorption capacity for pollutants and heavy metal ions, and has high selective adsorption capacity, which is crucial for removing heavy metal ions in the preparation process of battery-grade monoammonium phosphate, and helps to remove impurities from monoammonium phosphate solution and improve the purity of the product. In addition, the adsorbent can be regenerated and reused for adsorption, which reduces long-term operating costs and reduces solid waste generation. MCM-41@chitosan adsorbent combines the advantages of physical adsorbents and chemical adsorbents, and can achieve efficient removal of impurity ions in products. Chitosan, as a natural polymer material, is biodegradable and non-toxic, while MCM-41 nanomolecular sieve, as a pollution-free, environmentally friendly porous material, has low cost and is easy to mass produce, which further enhances its application potential in the field of environmental protection, making MCM-41@chitosan adsorbent more advantageous in environmental governance. At the same time, this application does not add any additional chemicals. This additive-free production method reduces the chemical burden on the environment and avoids toxic byproducts and waste that may be produced in traditional chemical treatment methods. It not only helps protect the environment, but also conforms to the current global pursuit of green chemistry and sustainable development. In this way, the preparation process of battery-grade monoammonium phosphate will not cause secondary pollution, ensuring the environmental friendliness of the entire application process, which is of great significance to the sustainability of chemical production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 XRD spectrum of the MCM-41 nanomolecular sieve prepared in Example 1. DETAILED DESCRIPTION

[0023] A highly efficient preparation method for battery-grade monoammonium phosphate based on composite material co-catalysis:

[0024] Embodiment 1:

[0025] Step 1, dissolving crude phosphoric acid and methanol in a blend, stirring until the mixture is uniform, settling for 2 hours, filtering the liquid to obtain filtrate 1, wherein the mass ratio of crude phosphoric acid to methanol is 1:0.8;

[0026] Step 2: adding ammonia water to the filtrate 2 of the filter assembly filled with aminated activated carbon to prepare a monoammonium phosphate solution, wherein the mass ratio of the filtrate 2 to the ammonia water is 1:0.8;

[0027] Step 3: Dissolve sodium alginate in 2-morpholineethanesulfonic acid buffer solution, stir magnetically for 3 hours, add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide, stir magnetically for 1 to 3 hours, add MCM-41 nanomolecular sieve, ultrasonicate for 30 to 120 minutes, add carboxymethyl chitosan, continue magnetic stirring for 3 to 5 hours to obtain a mixed viscous solution, add calcium nitrate solution drop by drop, and continue to add until the color changes to white, and filter to obtain water The gel was washed with ultrapure water for 3 times, and ultrapure water was added to cover the hydrogel. After freezing with liquid nitrogen, it was immediately placed in a vacuum freeze dryer for freeze drying and dried at -60°C for 24-48h, i.e., MCM-41@chitosan adsorbent, wherein the above raw materials are calculated by mass ratio as follows: sodium alginate: 2-morpholineethanesulfonic acid buffer solution: 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride: N-hydroxysuccinimide: MCM-41 nanomolecular sieve: carboxymethyl chitosan: calcium nitrate solution

[0028] =1:100:3:3:4:4:1, the concentration of 2-morpholineethanesulfonic acid buffer solution is 20mmol / L, and the mass percentage of calcium nitrate solution is 20%;

[0029] Step 4: Pass the monoammonium phosphate solution through a filter filled with MCM-41@chitosan adsorbent to obtain filtrate 3, and dry the filtrate 3 to obtain battery-grade monoammonium phosphate.

[0030] The preparation process of MCM-41 nanomolecular sieve includes the following steps:

[0031] Hexadecyltrimethylammonium bromide, triethanolamine, NaOH and deionized water are prepared into a mixed solution, stirred at 400 r / min at 40°C for 50 minutes, white carbon black is added into the mixed solution and stirred evenly, the pH value of the solution is adjusted to 10 with 1 mol / L HCl solution to obtain a mixed gel, and then the mixed solution is transferred into an open glass container, the glass container is placed in the lining of a reactor, 8 ml of deionized water is added outside the glass container, aged at 100°C for 48 hours under steam-assisted conditions, then crystallized at 150°C for 48 hours, washed and dried to obtain a crystalline product; the crystalline product is calcined at 550°C for 4 hours to obtain an MCM-41 nano molecular sieve.

[0032] The content of monoammonium phosphate in the monoammonium phosphate product is ≥99.5%, K≤0.008%, Ca≤0.003%, Na≤0.01%, Mg≤0.0003%, Zn≤0.0005%, Cu≤undetectable, Cr≤0.0002%, Ni≤undetectable, Mn≤0.0005%, AS undetectable, F - ≤0.0015%, SO 4 2- ≤0.005%, total content of water insoluble matter

[0033] ≤0.0003%.

[0034] Comparative Example 1:

[0035] The crude phosphoric acid and methanol were mixed and dissolved, and lime water with a mass fraction of 5% was added, and the mixture was stirred until the mixture was uniform. After 0.5 hours, the liquid was filtered to obtain filtrate 1, and the mass ratio of the crude phosphoric acid to the methanol was 1:0.8;

[0036] Ammonia water is added to the filtrate 1 to precipitate crystals, and the crystals are separated and dried to obtain ammonium phosphate, wherein the mass ratio of the filtrate 1 to the ammonia water is 1:0.8.

[0037] The content of monoammonium phosphate in the monoammonium phosphate product is ≥81%, K≤0.73%, Ca≤0.8%, Na≤2.3%, Mg≤0.04%, Zn≤0.032%, Cu≤0.023%, Cr≤0.012%, Ni≤0.018%, Mn≤0.036%, AS≤0.002%, F - ≤0.2%, SO 4 2- ≤0.15%, total water-insoluble content ≤0.001%.

Claims

1. A method for efficiently preparing battery-grade monoammonium phosphate based on composite material co-catalysis, characterized in that: The following steps are involved: Step 1, dissolving crude phosphoric acid and methanol, stirring until the mixture is uniform, settling for 0.5 to 2 hours, filtering the liquid to obtain filtrate 1; Step 2: adding ammonia water to the filtrate 2 of the filter assembly filled with aminated activated carbon to prepare a monoammonium phosphate solution, wherein the mass ratio of the filtrate 2 to the ammonia water is 1:0.6-1; Step 3, dissolve sodium alginate in 2-morpholineethanesulfonic acid buffer solution, stir magnetically for 3 hours, add 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide, stir magnetically for 1 to 3 hours, add MCM-41 nanomolecular sieve, ultrasonicate for 30 to 120 minutes, add carboxymethyl chitosan, continue magnetic stirring for 3 to 5 hours to obtain a mixed viscous solution, add calcium nitrate solution drop by drop, the color turns white and continue to add until the color no longer changes, filter to obtain a hydrogel, wash with ultrapure water 3 times, add ultrapure water to cover the hydrogel, and liquid After nitrogen freezing, it is immediately placed in a vacuum freeze dryer for freeze drying and dried at -60°C for 24-48h, i.e., MCM-41@chitosan adsorbent, wherein the above raw materials are calculated by mass ratio as follows: sodium alginate: 2-morpholineethanesulfonic acid buffer solution: 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride: N-hydroxysuccinimide: MCM-41 nanomolecular sieve: carboxymethyl chitosan: calcium nitrate solution = 1:50-150:0.8-9.5:1.5-4.5:1.5-5.6:2.3-10:0.5-1.5; Step 4: Pass the monoammonium phosphate solution through a filter filled with MCM-41@chitosan adsorbent to obtain filtrate 3, and dry the filtrate 3 to obtain battery-grade monoammonium phosphate.

2. The method for efficiently preparing battery-grade monoammonium phosphate based on composite material co-catalysis according to claim 1, characterized in that: In step 1, the mass ratio of the crude phosphoric acid to methanol is 1:0.5-0.

8.

3. The method for efficiently preparing battery-grade monoammonium phosphate based on composite material co-catalysis according to claim 1, characterized in that: In step 3, the concentration of the 2-morpholineethanesulfonic acid buffer solution is 15 to 30 mmol / L.

4. The method for efficiently preparing battery-grade monoammonium phosphate based on composite material co-catalysis according to claim 1, characterized in that: In step 3, the mass percentage of the calcium nitrate solution is 15% to 50%.

5. The method for efficiently preparing battery-grade monoammonium phosphate based on composite material co-catalysis according to claim 1, characterized in that: In step 3, the preparation process of the MCM-41 nanomolecular sieve comprises the following steps: The method comprises the following steps: preparing a mixed solution of hexadecyltrimethylammonium bromide, triethanolamine, NaOH and deionized water, stirring the solution at 400 r / min for 20 to 50 minutes at 40°C, adding white carbon black into the mixed solution and stirring the solution uniformly, adjusting the pH value of the solution to 10 to 11 with a 1 mol / L HCI solution to obtain a mixed gel, transferring the mixed solution into an open glass vessel, placing the glass vessel into the inner lining of a reaction kettle, adding 5 to 20 ml of deionized water outside the glass vessel, aging the solution at 85 to 100°C for 20 to 48 hours under steam-assisted conditions, crystallizing the solution at 150°C for 24 to 48 hours, washing and drying the solution, and calcining the solution at 500 to 550°C for 4 to 8 hours to obtain an MCM-41 nano molecular sieve.